A Conceptual Framework of Service Quality and Patient Loyalty in Muslim Friendly Healthcare - Azman, N.A.I.; Rashid, N.; Ismail, N.; Samer, S. (International Journal of Human and Technology Interaction (IJHaTI), 2020)
The purpose of this research is to investigate equalize of service quality in friendly Muslim hospitals and establish a conceptual framework that shows the relationship between service quality, patient satisfaction and loyalty. This research is founded on a comprehensive study of current literature on quality of hospital care, patient satisfaction, and patient loyalty. Important reviews of these literature studies have resulted in the determination and interpretation of service quality dimensions and the development of a relationship between service quality, patient satisfaction and patient loyalty. This paper determined five main aspects through which patients service quality in Muslim friendly hospitals.Thesefiveareasaretangibles,empathy, assurance, reliability and responsiveness. The framework indicates a direct link between quality of care, patient satisfaction and patient loyalty. Although many studies have been carried out on thestandardofhospitalservices,neitherofthem would do project all the possible dimensions to calculate the same in a friendly hospital in Malaysia. The SERVQUAL Model adopted by this study determines all the potential dimensions of service quality in Muslim friendly healthcare.